A Case Series of Bleeding Complication Post Percutaneous Dilatational Tracheostomy and Management - Lubis, Batian; Purwaamidjaja, Dis Bima P; Lestari, Mayang Indah; Faisal; Thamrin, Muhammad Husni; Belinda, Febri Akhmad (Journal of Society Medicine, 2023)
Introduction: Percutaneous Dilatational Tracheotomy (PDT) is a procedure established for the management of airway and ventilation in the medium to long term for critically ill patients in the ICU. Bleeding is one of the most frequent early complications of tracheostomy. The comorbid conditions of critically ill patients increase the risk of bleeding complications. The aim of this case was to identify factors that increase the risk of bleeding complications in critically ill patients undergoing Percutaneous Dilatational Tracheostomy (PDT) and its management Case: Two cases of patients experiencing bleeding complications after PDT were reported. The bleeding in these patients were suspected to be caused by coagulation disorders due to sepsis and chronic kidney disease. The bleeding occurred on day-1 and 2 post-PDT procedure. Bleeding complications that were not resolved with general management were managed by subcutaneous suturing in the anatomical region of branching arteries and veins that supply the trachea. Conclusion: Bleeding after PDT are a part of early complications of tracheostomy procedures. This complication is more often found in critically ill patients. Management can be carried out by suturing the anatomical region of branching arteries and veins supplying the trachea.